Influence of systemic diseases on post-endodontic repair (Research, Society and Development, 2024)
Systemic diseases are conditions that impact several organ systems, affecting the immune system of those who suffer from them. At the oral level, these diseases manifest signs and symptoms which, combined with the deficiency in the patients' defense mechanisms and alterations in the healing processes, directly influence the efficacy of treatments aimed at addressing endodontic pathologies. The purpose of this research is to review selected literature addressing the influence of systemic diseases (diabetes, HIV, cardiovascular diseases, autoimmune diseases, inflammatory bowel diseases and smoking) on post-endodontic repair. Materials and methods: Information was obtained by searching databases such as Pubmed, Google Scholar, Scopus, EBSCO host, Science Direct, Elsevier and ResearchGate, selecting research according to inclusion and exclusion criteria. Results: Systemic diseases such as diabetes, cardiovascular disease, HIV infection, inflammatory bowel disease and smoking can interfere with the repair process of periapical tissues after endodontic treatment. Conclusions: The impact of systemic diseases on the repair process following endodontic treatment is suggested. However, further longitudinal studies are required to evaluate the effect of systemic diseases on periapical healing.  In addition, the importance of knowledge about the systemic health of patients is highlighted as it may alter the outcome of endodontic infection treatment.